Taboo Words Related to Parahyangan, Pawongan, and Palemahan Used in Bebetin Village - Sathya, Widhi Mas (Jurnal Ilmu Multidisiplin Indonesia, 2024)
The objective of this research was to recognize and examine the forbidden terms present in the Balinese language as spoken in Bebetin Village. The study adopted a descriptive qualitative research, selecting three informants according to the criteria outlined by Samarin, 1967. The taboo words found in Bebetin Village are related to the Tri Hita Karana concept, namely Parahyangan, Pawongan, and Palemahan. Parahyangan refers to the relationship between humans and God as the creator and sustainer of their existence, Pawongan encompasses human interactions in the social realm, and Palemahan centers on the connection between humans and their natural surroundings. The findings revealed 46 taboo words in use within Bebetin Village, categorized into 2 terms associated with connections to God, 37 terms linked to human harmony, and 8 terms related to environmental harmony.